Edukasi tentang Potensi Daun Sambiloto sebagai Penguat Sistem Imun Tubuh terhadap Covid-19 - Sianipar, Erlia Anggrainy; Marcella, Sherleen; Liliana, Merry; Tiono, Yovita viona; Edyson, Dino Claudio Signory Putra; Buntoro, Leonardo; Nanda, Karmill Tri; Siswandi, Alodia Jeconiah (Poltekita: Jurnal Pengabdian Masyarakat, 2023)
The immune system greatly influences the increasing positive cases and death of Covid 19. In order to increase public knowledge about the use of herbal plants as a booster for the immune system, the Pharmacy Study Program at the Atma Jaya Catholic University of Indonesia was holding activities for community dedication by providing education about the potential of Sambiloto leaves in preventing Covid-19 infection. This education was aimed at social media users, given a seven-minute video shared on Youtube. The video link was shared through social media Instagram, WhatsApp, and Line. The video was uploaded to Youtube on April 18, 2021, then after two weeks, followed by filling out a questionnaire by the viewers using a Google form until May 2, 2021. The results show that 1,929 viewers, 354 likers, and 305 respondents filled out the questionnaire. The questionnaire results also showed that over 90% of respondents increased their knowledge after watching the video and could answer all the questions correctly. Thus, it can be concluded that this educational activity has succeeded in increasing the knowledge of social media users significantly and had a positive impact on changing people's behavior for using sambiloto leaves as immune boosters for the prevention and treatment of covid 19.